Unveiling The Dynamics of Women's Empowerment: An In-Depth Critical Review - Paul, Saima (International Journal of Psychosocial Rehabilitation, 2020)
Empowerment of women for development is a crucial step towards actualizing sustainable development. The present paper brings a systematic literature review of women's empowerment that involves an analysis of women's empowerment in general, worldwide and in India. The analyzed literature was divided into international literature and Indian literature based on the subject area, and then authors and articles were systematically reviewed to draw out similarities in the findings. This review reveals that women have a higher societal status in traditional domains of work in developing countries. However, they need to be empowered more in terms of decision-making, and hence, they should focus on awareness and capacity building. In India, political reservations for women have positive impacts regarding women's political representation, particularly in the decision-making process of the state; however, problems like violence against women and the problem of weakness in policy representation still arise frequently. The results outlined economic, educational, and political participation as significant elements for promoting gender equality. The review highlights the necessity of establishing multiple, high-quality indices that reflect all facets of empowerment while underlining the need to conduct research that would be most relevant for particular cultural contexts. In the future, there must be more prospective research on a combination of gender, the effects of the use of technology, and the involvement of male peasants in the betterment of gender equity. Since these areas are addressed, researchers and policymakers can develop insights into women's rights, drawing on more positive, efficient, and enduring efforts to advance women. This work shall examine the current state of women empowered in India from a human rights perspective, relying on attributes like control over household decisions, level of economic independence, mobility, voting rights, tolerability of gender inequality, media interaction, education, and experience of physical violations. These research outcomes fill the literature gap, contributing to the agenda on gender equality with a practical understanding of the situation in India and presenting directions for further development.